If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -6(3x + 14) = 147 Reorder the terms: -3x + -6(14 + 3x) = 147 -3x + (14 * -6 + 3x * -6) = 147 -3x + (-84 + -18x) = 147 Reorder the terms: -84 + -3x + -18x = 147 Combine like terms: -3x + -18x = -21x -84 + -21x = 147 Solving -84 + -21x = 147 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '84' to each side of the equation. -84 + 84 + -21x = 147 + 84 Combine like terms: -84 + 84 = 0 0 + -21x = 147 + 84 -21x = 147 + 84 Combine like terms: 147 + 84 = 231 -21x = 231 Divide each side by '-21'. x = -11 Simplifying x = -11
| -6x+4-3+x=11 | | 12-3=7(n-4)+5n | | (-14)(0.22)+(-16)(0.65)=(-18)(0.13) | | 8x+7y-3x= | | -2x-2(7x-16)=-10 | | 4y+4=-2x | | 14-4X=5=X/2 | | y-0.65y=3500 | | 7x+25*2=127 | | 40=2mxn | | 0.1x+x=2.75 | | 4x+32x+1=0 | | -4+5n=6 | | 3x-46x+1=0 | | n+17.9=18.3 | | 15d-8d+13=55 | | x-10=7.2 | | (x^5)-i=0 | | 2x-1x+3=0 | | 12-48n^2= | | 0.87=(0.13*2^x)/x! | | x/7-1=0 | | 3x^2-30x=69 | | -3x-4(-6x-10)=187 | | 7x^2y+14xy=7xy(x+2) | | X^2-10x+75=98 | | abs-x^2-3x+5abs=-4 | | 2+14n=17+10n+5n | | -6x+6(4x-12)=-198 | | M/-5-3 | | I-x^2-3x+5I=-4 | | 3k=9+2k |